Cross-disciplinary communication between oral and gut microbiota in head and neck cancer - Lin, Xinhua; Qin, Hanbin; Liu, Zhonglu; Zhao, Xin; Liu, Xuexia; Zhang, Hua (Frontiers in Oncology, 2026)
Head and neck cancer (HNC) is a prevalent malignancy with a rising global incidence. While traditional risk factors such as tobacco use and viral infections are well-established, the dysbiosis of oral and gut microbiota has recently emerged as a pivotal contributor to HNC pathogenesis. The oral-gut axis serves as a critical conduit for bidirectional microbial crosstalk, facilitated by bacterial translocation, metabolic exchange, and immune modulation, collectively fostering a pro-tumorigenic microenvironment. Key oral pathogens, including Fusobacterium nucleatum and Porphyromonas gingivalis, exacerbate chronic inflammation, promote immune evasion, and activate oncogenic signaling pathways such as Wnt/β-catenin, MAPK/ERK, and PD-1/PD-L1. In parallel, gut dysbiosis influences HNC progression by altering the production of microbial metabolites, including short-chain fatty acids, bile acids, and tryptophan derivatives, which systemically regulate inflammation and anti-tumor immunity. Growing evidence also implicates the microbiota in modulating responses to radiotherapy, chemotherapy, and immunotherapy. Therapeutic strategies targeting the oral-gut axis, including probiotics and antimicrobial peptides, hold promise for alleviating treatment-induced mucosal injury and improving therapeutic outcomes. Nonetheless, significant challenges persist, including elucidating network-level microbial interactions, validating robust biomarkers, and advancing these findings into clinical practice. Future multidisciplinary collaborations are essential to fully leverage the oral-gut microbiota axis for precision oncology in HNC.